Fit testing and comfort evaluation of prophylactic dressing use for healthcare workers under N95/P2 respirators in one health service district in Australia. (May 2022) - Barakat-Johnson, M.; Stephenson, J.; Dempsey, K.; Innes, L.; Jain, S.; Leong, T.; Schouten, T.; Coyer, F.; Hallahan, A.
Summary: Background: This study evaluated the use of prophylactic dressings (silicone foam, silicone tape, hydrocolloid) under N95/P2 respirators to determine which dressings fit successfully. Aim: The aim was to develop a health service protocol for one state in Australia. Methods: Data were collected during August and September 2021 as part of the Respiratory Protection Programme on 600 health workers using three types of prophylactic dressings. Five different types of respirators were used. Participant healthcare workers rated comfort on a four-point Likert scale. Results: Successful fit was achieved by 63.6% of the respirator-dressing combinations. The best-performing respirator-dressing combination was the Trident® respirator with dressing Mepilex® Lite silicone foam (90.2% pass rate). High pass rates were found in the Trident® respirator with Mepilex® Border Lite with SofSicure silicone tape (79.1%); the 3M™ 1860 respirator with Mepilex® Border Lite with SofSicure silicone tape (74%); and the BSN orange duckbill respirator with Mepilex® Lite silicone foam (69.8%). The poorest-performing combination was the BYD™ respirator with Mepilex® Border Lite with SofSicure silicone tape (25.9% pass rate). Uncorrected chi-squared tests for association revealed significant associations between dressing type and outcome ( P =0.004) and respirator type and outcome ( P <0.001). Most respondents (82%) found the dressing combination markedly comfortable. Conclusions: When using prophylactic dressings under N95/P2 respirators, it is necessary to perform a fit test. In this study Trident® respirators had the highest probability of successful fit, while BYD™ respirators had the lowest. Combining Trident® respirators with Mepilex® Lite dressing was optimal. Most participants reported greater comfort with the dressings under the respirators.